2012
DOI: 10.1590/s0104-14282012005000068
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable starch-based films containing saturated fatty acids: thermal, infrared and raman spectroscopic characterization

Abstract: Biodegradable films of thermoplastic starch and poly (butylene adipate co-terephthalate) (PBAT) containing fatty acids were characterized thermally and with infrared and Raman spectroscopies. The symmetrical character of the benzene ring in PBAT provided a means to illustrate the difference between these spectroscopic techniques, because a band appeared in the Raman spectrum but not in the infrared. The thermal analysis showed three degradation stages related to fatty acids, starch and PBAT. The incorporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 22 publications
(26 reference statements)
1
21
0
1
Order By: Relevance
“…Bilck et al [22] found WVP values of 4.22 × 10 -6 g / m.Pa.day and Nobrega et al [15] found 8.07 × 10 -6 g / m.Pa.day, using a 33%-64% RH gradient across the film. Also Olivato et al [23] evaluated the WVP in films of starch/PBAT (50:50) using 0-75% as RH gradient and reported values of 5.4 × 10 -6 g /m.Pa.day for WVP.…”
Section: Water Vapour Permeability (Wvp)mentioning
confidence: 99%
See 2 more Smart Citations
“…Bilck et al [22] found WVP values of 4.22 × 10 -6 g / m.Pa.day and Nobrega et al [15] found 8.07 × 10 -6 g / m.Pa.day, using a 33%-64% RH gradient across the film. Also Olivato et al [23] evaluated the WVP in films of starch/PBAT (50:50) using 0-75% as RH gradient and reported values of 5.4 × 10 -6 g /m.Pa.day for WVP.…”
Section: Water Vapour Permeability (Wvp)mentioning
confidence: 99%
“…This behaviour could be associated with the glycerol composition; the BDG had approximately 25% more glycerol than the others (Table 1), and, consequently, had proportionally more plasticiser that created its higher hygroscopic surface. Other researchers reported that starch-based films had increased hygroscopic characteristics with increased glycerol concentrations and associated this process with an increase in hydroxyl groups available to make hydrogen bonds with water [4,[13][14][15] . Białopiotrowicz [26] examined the contact angle in corn and potato starch films at different concentrations (2, 4, 6, 8, 10 and 12%wt) for different liquids (water, glycerol, formamide, ethylene glycol and diiodomethane poly(methyl methacrylate)) and reported that the contact angles decreased linearly with increasing starch concentration.…”
Section: Contact Anglementioning
confidence: 99%
See 1 more Smart Citation
“…algunos picos característicos de Alm y AE, pero la intensidad de estos es diferente. La señal de los grupos OH de las muestras Alm-AE, es menor que la del Alm, la señal de C=O (grupos ácidos) de las muestras Alm-AE es de menor intensidad que la del AE, además aparece un poco desplazada (1713 cm -1 ); esta señal ha sido asignada a carbonilo de esteres y ácidos en mezclas de ácido esteárico, glicerol, Alm y poli(adipato de butileno-co-tereftalato) [13]. La señal debida a la flexión de los grupos OH que exhibió el Alm a 1643 cm -1 , presentó una disminución en las muestras de Alm-AE.…”
Section: Resultados Y Análisisunclassified
“…This trend is noticed in polymers based on starch as well. The raising of glycerol content increases the hydrophilicity of these films, which might be related with the OH functional groups of the glycerol [30][31][32][33] . Figure 5 presents the images of scanning electron microscopy of the polymers with hydrophobic characteristics on the fracture surface of the TPS samples, according to Table 6.…”
Section: Starch Modified With Silicamentioning
confidence: 99%